2016
DOI: 10.1002/ecs2.1621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dams and geomorphic context on riparian forests of the Elwha River, Washington

Abstract: Abstract. Understanding how dams affect the shifting habitat mosaic of river bottomlands is key for protecting the many ecological functions and related goods and services that riparian forests provide and for informing approaches to riparian ecosystem restoration. We examined the downstream effects of two large dams on patterns of forest composition, structure, and dynamics within different geomorphic contexts and compared them to upstream reference conditions along the Elwha River, Washington, USA. Patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 77 publications
1
33
0
Order By: Relevance
“…On one hand, the predictable monomodal flood pulse of the Abacate River and the periodic flooding of its forest at high elevations allowed the establishment of plants with morphological, physiological, and phenological adaptations to flooding (Junk et al, 1989; FIGURE 7 Fisher's alpha diversity in the two areas of Uatumã Sustainable Development Reserve. Thus, the construction of the dam in Uatumã area may have altered the lateral connectivity of the river stretch downstream, reducing seed migration, an important phenomenon that contributes to high habitat diversity in floodplains (Shafroth, Perry, Rose, & Braatne, 2016;Ward & Stanford, 1995;Ward, Tockner, & Schiemer, 1999). SA, adults; SB, saplings; and SC, seedlings.…”
Section: Diversity Between Areas and Topographic Levelsmentioning
confidence: 99%
“…On one hand, the predictable monomodal flood pulse of the Abacate River and the periodic flooding of its forest at high elevations allowed the establishment of plants with morphological, physiological, and phenological adaptations to flooding (Junk et al, 1989; FIGURE 7 Fisher's alpha diversity in the two areas of Uatumã Sustainable Development Reserve. Thus, the construction of the dam in Uatumã area may have altered the lateral connectivity of the river stretch downstream, reducing seed migration, an important phenomenon that contributes to high habitat diversity in floodplains (Shafroth, Perry, Rose, & Braatne, 2016;Ward & Stanford, 1995;Ward, Tockner, & Schiemer, 1999). SA, adults; SB, saplings; and SC, seedlings.…”
Section: Diversity Between Areas and Topographic Levelsmentioning
confidence: 99%
“…, Shafroth et al. ). The lack of sediment delivery to the coast contributed to altered sediment transport (Miller et al.…”
Section: Introductionmentioning
confidence: 99%
“…The two dams on the Elwha River had large impacts on downstream habitats because sediment, habitat-forming LWD, and nutrients were sequestered behind the dams , Shafroth et al 2016. The lack of sediment delivery to the coast contributed to altered sediment transport ) and erosion of coastal beaches (Warrick et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The original plant communities have been gradually replaced by those dominated by perennial and annual herbaceous species (Fan et al., ; Wang et al., ; Ye, Zhang, Deng, & Zhang, ). Therefore, the detailed knowledge of the eco‐physiological processes underlying their dominance is critical to understanding the community assembly mechanism of this riparian ecosystem, as well as improving restoration practices (Fraaije, Braak, Verduyn, Verhoeven, & Soons, ; Garssen, Baattrup‐Pedersen, Voesenek, Verhoeven, & Soons, ; Shafroth, Perry, Rose, & Braatne, ).…”
Section: Introductionmentioning
confidence: 99%
“…The original plant communities have been gradually replaced by those dominated by perennial and annual herbaceous species Wang et al, 2012;Ye, Zhang, Deng, & Zhang, 2013). Therefore, the detailed knowledge of the eco-physiological processes underlying their dominance is critical to understanding the community assembly mechanism of this riparian ecosystem, as well as improving restoration practices (Fraaije, Braak, Verduyn, Verhoeven, & Soons, 2015;Garssen, Baattrup-Pedersen, Voesenek, Verhoeven, & Soons, 2015;Shafroth, Perry, Rose, & Braatne, 2016). Jie, Fan, Xie, Zhang, and Xiong (2012) have measured the leaf traits of 42 species in the riparian zone of the Three Gorge Reservoir Area (TGRA) and found that these traits were restricted to the lower-investment and faster-return end of the global leaf spectrum, which are typical characteristics of fast-growing species (Wright et al, 2004).…”
Section: Introductionmentioning
confidence: 99%